A Survey of Oral Cavity Afferents to the Rat Nucleus Tractus Solitarii - Corson, James (2012)
Visualization of myelinated fiber arrangements, cytoarchitecture, and projection fields of afferent fibers in tandem revealed input target selectivity in identified subdivisions of the nucleus tractus solitarii (NTS). The central fibers of the chorda tympani (CT), greater superficial petrosal (GSP), and glossopharyngeal (IX) nerves, three nerves that innervate taste buds in the oral cavity, prominently occupy the gustatorysensitive rostrocentral subdivision. In addition, CT and IX innervate and overlap in rostrolateral subdivision, which is primarily targeted by the lingual branch of the trigeminal nerve (LV). In rostrocentral subdivision, compared to the CT terminal field in rostrocentral subdivision, GSP appeared more rostral and medial, and IX was more dorsal and caudal. While IX and LV filled the rostrolateral subdivision diffusely, CT projected only to the dorsal and medial portions. The intermediate lateral subdivision received input from IX and LV but not CT or GSP. In the caudal NTS, the ventrolateral subdivision received notable innervation from CT, GSP, and LV, but not IX. No caudal subnuclei medial to solitary tract contained labeled afferent fibers. The data indicate selectivity of fiber populations within each nerve for functionally distinct subdivisions of the NTS, highlighting the possibility of equally distinct functions for CT in the rostrolateral NTS, and CT and GSP in the caudal NTS. Further, this provides a useful anatomical template to study the role of oral cavity afferents in the taste-responsive subdivision of the NTS as well as in subdivisions that regulate ingestion and other oromotor behaviors.